Determining whether a phosphatic concretion containing a Cretaceous juvenile crocodylian is a coprolite or a non-fecal concretion - Ryan C. Allen; Karen Chin; Mike Zawaski; Joseph J. Bevitt; Wayne Smiglewski (Scientific Reports)
Abstract Phosphatic concretions in terrestrial settings are often identified as coprolites based upon their biotic contents and high phosphorus levels. However, recent discoveries have shown that non-fecal origins of fossiliferous phosphatic concretions are more common than originally recognized. Confusion about the taphonomic origin of phosphatic concretions can lead to erroneous paleobiological and paleoenvironmental interpretations, so a set of criteria would be useful to evaluate whether a phosphatic concretion is a coprolite. Here we describe a phosphatic concretion containing a small crocodylian from the Upper Cretaceous Hell Creek Formation and assess its origin, formation, and paleobiological implications. We conducted neutron computed tomography (CT) on the skull-bearing portion of the concretion, and analyzed the geochemical composition of the concretion with electron microprobe, µ-XRF, and fusion ICP-OES. In this study, the completeness and distribution of the skeletal elements present a stronger case for a non-fecal origin. This scenario suggests minimal transport after death and deposition. Neutron CT analysis of the crocodylian skull supports its referral to Brachychampsa montana, and allows inferences regarding body length, age, and dietary habits. Although coprolites and non-fecal concretions can be difficult to differentiate, unique features can reflect differences in origin that offer different types of taphonomic and paleobiological information.